(untitled) (Вісник: Міжнародні відносини, 2025)
Introduction. In the final period of the First World War and in its aftermath, Europe underwent significant transformations characterized by profound geopolitical shifts and the determination of the political future of the newly established states in Central and Eastern Europe. The British Empire and its political leaders played one of the key roles during this time. Among them, a particularly prominent figure was Winston Churchill, who held various governmental positions. The aim of this study was to analyze Churchill’s diplomatic activity and to examine his perception of Ukraine in 1917–1921. Methods. The methodological framework of the research is based on historical-genetic, problem-chronological, comparative-political, and discourse analysis. The source base includes memoir literature, official government documents, parliamentary debates, diplomatic correspondence, and Churchill’s speeches. Results. The study analyzes the period of revolutionary transformations that led to the collapse of imperial entities and the formation of new national states in Eastern Europe. It has been established that Churchill played a key role in shaping the policy of containing Bolshevism during the stage of postwar reconstruction of the international system. Particular attention is paid to his initiatives regarding military and diplomatic support of the White movement, the deployment of interventionist operations, and attempts to legitimize anti-Bolshevik governments within the framework of international law. At the same time, it has been demonstrated that Churchill did not perceive Ukraine as an independent political subject but viewed it exclusively through the lens of the internal crisis of a “united Russia”, which, in his opinion, should be restored through support for the White movement. The study highlights the substantive characteristics of Churchill’s foreign policy rhetoric, his efforts to consolidate the Entente allies around the concept of ideological confrontation with Bolshevism, and also the transformation of the diplomatic strategy of the British Empire under conditions of changing geopolitical balance of power. A comparative analysis of Churchill’s position and the general course of David Lloyd George’s government has been conducted. Conclusions. It has been established that Churchill’s geopolitical logic was based on the idea of stability through the support of great powers and the restoration of imperial formats, within which Ukrainian statehood was regarded as a temporary and premature political entity.